Impact of Neoadjuvant Chemotherapy on Tumor and Nodal Response in Breast Cancer-An Observational Study - Masum, Kumar; Thomas, Shibi Mary; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Introduction: Breast cancer is common in India, with variable responses to Neoadjuvant Chemotherapy (NACT), which is essential for tumor downstaging, breast conservation, and prognostic assessment. This study evaluated the effectiveness of NACT in reducing lymph node positivity in breast cancer patients. Materials and Methods: An ambispective observational study was conducted over six months at a tertiary care oncology center, including 70 adult female breast cancer patients who received NACT followed by surgery. Clinical, demographic, tumor, and treatment data were collected from medical records. Tumor staging followed AJCC TNM criteria, and treatment response was assessed clinically and pathologically. Statistical analysis evaluated associations with pathological complete response, with p < 0.05 considered significant. Results: Among 70 breast cancer patients, 65.7% were aged over 50 years and approximately 80% were postmenopausal, with most presenting at stage II (52.8%) or stage III (40.0%). Overall response to neoadjuvant chemotherapy was observed in 68.6% of patients, including a pathological Complete Response rate (pCR) of 28.6%. Higher pCR rates were noted in HR−/HER2+ and triple-negative subtypes. Tumor size ≤2 cm (p < 0.001) and clinical nodal stage (p = 0.03) were significant predictors of response, while grade III toxicities were low and comparable across regimens. Conclusion: This study demonstrates that NACT demonstrated pCR rates comparable to international data, especially in HER2-positive and triple-negative breast cancer. Treatment response was primarily influenced by tumor biology and size rather than demographic factors, and limited breast conservation highlights the importance of early detection and supportive care.
Keywords: Breast cancer; Neoadjuvant chemotherapy; Pathological complete response; TNBC; HER2; AJCC